2019
DOI: 10.1111/jsap.13089
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of complications associated with surgically‐placed gastrostomy tubes in 43 dogs with septic peritonitis

Abstract: Objectives:To determine the safety of surgically-placed gastrostomy feeding tubes in dogs with septic peritonitis.Materials and MethOds: Retrospective analysis of 43 dogs with septic peritonitis that had undergone surgical exploration and gastrostomy tube (de Pezzer or Foley) placement as part of the surgical procedure. Postoperative recovery times, hospitalisation times, complication rates and overall survival times were documented. results: The most common cause of septic peritonitis was dehiscence of an ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…Previous studies with surgically placed gastrostomy tubes have reported a minor complication rate of 26%-75%, a major complication rate of 0%-25%, and an overall complication rate as high as 33.3%. 29,30 In our study, 2/12 dogs developed minor complications, which is similar to previous reports; major complications occurred in 4/12 dogs and overall complications occurred in half the dogs that survived to discharge, both higher than previous reports. 29,30 The high tube complication rate warrants further investigation.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Previous studies with surgically placed gastrostomy tubes have reported a minor complication rate of 26%-75%, a major complication rate of 0%-25%, and an overall complication rate as high as 33.3%. 29,30 In our study, 2/12 dogs developed minor complications, which is similar to previous reports; major complications occurred in 4/12 dogs and overall complications occurred in half the dogs that survived to discharge, both higher than previous reports. 29,30 The high tube complication rate warrants further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…29,30 In our study, 2/12 dogs developed minor complications, which is similar to previous reports; major complications occurred in 4/12 dogs and overall complications occurred in half the dogs that survived to discharge, both higher than previous reports. 29,30 The high tube complication rate warrants further investigation. The 4 major tube complications in this series of dogs appear to be unrelated in mode of failure.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations